A study on the effect of firearms on the hearing of military personnel - Mohd Zambri, Ibrahim (2008)
The aim of this study was to establish the prevalence of hearing impairment and transient effect of ear pathology among the army personnel who underwent firearm training without wearing hearing protection. A prospective cross-sectional study was carried out in RMAF 16 Melayu Infantry unit of Desa Pahlawan camp, Kelantan and from infantry unit of 301 camp, Tanah Merah , Kelantan, from July 2007 till October 2007. The population was taken from an army personnel who involved in firearm training.The subject's particulars and history takings were recorded and compiled. The subject's were examined by using otoscope, tymponometry, portable audiometry and otoacoustic emission (DPOAE) and findings were recorded. Evaluation and examination was performed in three stage , pre shooting , post shooting less than 48 hours and post shooting more than 2 weeks. Hearing threshold above 30 db at any frequencies was considered hearing impairment. A total number of 210 army personnel were involved in this study. All were males. The age range was from 21 years to 47 years old. The prevalence for post shooting of the right middle ear effusion was 21.1% and for left 20%. Majority of the hearing impairment occured at frequency of 6 kHz for both ears, 50.5% for right ear and 67% at left ear. The prevalence of temporary threshold shift was 26% for right ear and 21.4% for left ear. For permanent threshold shift, the prevalence for right and left ear was 11% and 8.1 %. Those who were right handed shooter gave a significant p value < 0.05, caused hearing impairment to the left ear. There was strong relation between age, duration of work and frequency of firearm training causing hearing impairment, with p value < 0.05. Results from this study indicate that there is an urgent need from the Ministry of Defense to develop appropriate intervention or hearing conservation program in order to prevent army personnel from developing the noise induced hearing loss